2016
DOI: 10.1111/mpp.12405
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the in planta Phakopsora pachyrhizi secretome and potential effector families

Abstract: Asian soybean rust (ASR), caused by the obligate biotrophic fungus Phakopsora pachyrhizi, can cause losses greater than 80%. Despite its economic importance, there is no soybean cultivar with durable ASR resistance. In addition, the P. pachyrhizi genome is not yet available. However, the availability of other rust genomes, as well as the development of sample enrichment strategies and bioinformatics tools, has improved our knowledge of the ASR secretome and its potential effectors. In this context, we used a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 75 publications
(117 reference statements)
1
23
0
Order By: Relevance
“…When 58 transcripts were compared to the secreted sequences identified by Link et al (2014) in the haustorium transcriptome of P. pachyrhizi , it was possible to identify 44 sequences similar to 12 of the transcripts that were predicted as secreted. In addition, three transcripts that were found among the top expressed transcripts common to both genotypes (de_novo_2238, de_novo_5381, and de_novo_5849) were also functionally validated by Carvalho et al (2016) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When 58 transcripts were compared to the secreted sequences identified by Link et al (2014) in the haustorium transcriptome of P. pachyrhizi , it was possible to identify 44 sequences similar to 12 of the transcripts that were predicted as secreted. In addition, three transcripts that were found among the top expressed transcripts common to both genotypes (de_novo_2238, de_novo_5381, and de_novo_5849) were also functionally validated by Carvalho et al (2016) .…”
Section: Resultsmentioning
confidence: 99%
“…Each cap was used for pulses ranging from 1500–2000 corresponding to the collection of approximately the same number of cells. Samples were collected for both resistant and susceptible plants ( Carvalho et al , 2016 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, six candidates showed suppression of plant cell death triggered by Pseudomonas syringae pv. tomato DC3000 and an accumulation in nucleus and cytosol after transient expression in N. benthamiana (de Carvalho et al ., ). In another study, two out of six selected candidates were found to increase P. infestans infection in N. benthamiana , suggesting a role in the virulence of the soybean rust fungus (Kunjeti et al ., ).…”
Section: Functional Characterization Of Rust Effectorsmentioning
confidence: 97%
“…In C. fulvum , cys-rich effectors can inhibit and protect against plant hydrolytic enzymes, such as proteases, glucanases, and chitinases [32]. Cys-rich small-secreted proteins have also been identified as major effectors in the obligate biotrophic pathogens Melampsora larici-populina [35], and the Asian soybean rust fungus Phakopsora pachyrhizi [42], where one of the cys-rich small proteins identified as an effector has been shown to suppress plant immunity [43]. …”
Section: Where and How To Look For Effectors?mentioning
confidence: 99%